Análise dos elementos do espaço geográfico no Projeto Executivo de Enquadramento de Corpos de Água em Classes e Plano de Bacia para os rios Santa Maria da Vitória e Jucu-ES - Salaroli, Douglas Rafael (2013)
This research is the completion of the dissertation carried out with the financial support of the Foundation for Research Support of Espírito Santo (FAPES). We discussed the " Executive Project for the Environment Watercourse and Basin Plan for Santa Maria da Vitória and Jucu rivers" (PEEPB), both in the state of Espírito Santo. The PEEPB is an innovative attempt towards a shared public management of water in this state. Covers beyond the Watershed Committees, actors managers par excellence, and also include the Federal University of Espírito Santo (UFES) with the Laboratory of Water Resources Management and Regional Development (LABGEST_DEA_UFES), the Institute of the Environment and Water Resources of Espírito Santo (IEMA), and partnership with a consultant of shared management of water resources Paulo Paim. This team of technical and scientific support works in the training of managers, in making proposals for social, institutional and political mobilization, and on the orientation of planning and ordainment of hydrographic territories to carry out the water bodies framing in class and the Watershed Plan. According to the Law of Waters (9433/97) and the Water Resources State Policy (Law 5818) the participation of three segments of society: the government, the community and water users, are gueranteed to act in the management of water resources in order to promote an egalitarian and participatory process. Given the large number of actors that these segments represent at the watershed committees, and the institutional partnership for the capacity building of these managers to carry out the project of Water Bodies Framework and watershed plan, lies this research. Our goal is to study the activities of PEEPB in an attempt to understand the processes of production of water space, in this direction we use as a method the study of the elements of geographical space, as follows: "Men, firms, institutions, the ecological environment "(Santos, 2008), as an articulated process in itself and each other. We classified the elements of space into categories of qualitative variables as actors, the function performed at PEEPB, goal of the action and the correlation with other elements, which facilitated the methodology towards the understanding of the studied elements of space and their relations in PEEPB. From this, we observed that the relations between the elements of the space are able to expose to water management forms of recognition of the diversity of actors managers of hydrographic territory . The amplitude is to absorb the instances of thought between actors acting the horizontality and verticality in the process of planning PEEPB a social production of space waters based on otherness.